Structural design of pavements incorporating foamed bitumen mixtures - Kuna, Kranthi; Airey, Gordon; Thom, Nick (Institution of Civil Engineers Publishing, 2017)
This paper presents a rational structural design methodology termed the ‘cumulative damage approach’ for road, port and airport pavements incorporating cold bituminous mixtures with foamed bitumen. This has been developed along with a laboratory test, the uniaxial indirect tensile test, to evaluate the fatigue characteristics of these mixtures. The test was developed with a view to addressing the limitations of conventional fatigue tests for foamed bitumen mixtures. The new design approach takes account of the actual stiffness evolution of the mixtures obtained from the fatigue test. It is compared with a traditional approach for conventional flexible pavements, which is based on pavement life as a function of computed tensile strain in the material and interpretation of fatigue data in a conventional way. The results show that the traditional design approach yields conservative outcomes for pavements with foamed bitumen mixtures if the same transfer function or shift factor used for hot mix asphalt is applied. The results also show that if all factors other than induced load influence are the same, the shift factor for foamed bitumen mixtures could be 25–35% higher than for hot mix asphalt.